International Transfer Pricing and Performance of Supranational Companies in Nigeria West Africa - OSHO, Augustine Ejededawe; ADEWOLE, Felix Ibukun (Annals of Spiru Haret University. Economic Series, 2022)
The study examined the relationship between international transfer pricing and the performance of supranational companies in Nigeria. The study used secondary data from the Central Bank of Nigeria (CBN) Statistical Bulletin, the Federal Inland Revenue Service (FIRS), the World Bank Statistical Bulletin, and annual reports and accounts of the sampled multinational companies. The study used panel regression analysis. The results of the study showed that interest rates and import duties have a significant and positive effect on the performance of supranational corporations in Nigeria. The study further found that corporate income tax and exchange rate have a significant and negative impact on the performance of supranational corporations in Nigeria. Based on the results, the study concluded that international transfer pricing has a significant impact on the performance of supranational companies in Nigeria, particularly when international transfer pricing is measured using interest rates, exchange rates, corporate income taxes and import duties; while performance is measured by profit after tax. The study therefore recommended that supranational companies should develop a system to defend themselves against exchange rate and corporate taxes caused by unforeseen exchange rate movements and double taxation.